Novel findings in context of molecular diversity and abundance of bacteriophages in wastewater environments of Riyadh, Saudi Arabia. - Fahad Alanazi; Islam Nour; Atif Hanif; Ibrahim Al-Ashkar; Reem M Aljowaie; Saleh Eifan (PLoS ONE, 2022)
The diversity among bacteriophages depends on different factors like ecology, temperature conditions and genetic pool. Current study focused on isolation, identification and diversity of phages from 34 sewage water samples collected from two different wastewater treatment plants (WWTPs), King Saud University wastewater treatment plants (KSU-WWTP) and Manfoha wastewater treatment plants (MN-WWTP) in Riyadh, Saudi Arabia. Samples were analyzed by PCR and Next Generation Sequencing (NGS). Siphoviridae, Podoviridae and Myoviridae families were detected by family-specific PCR and highest prevalence of Myoviridae 29.40% was found at MN-WWTP followed by 11.76% at KSU-WWTP. Siphoviridae was detected 11.76% at MN-WWTP and 5.88% at KSU-WWTP. Lowest prevalence for Podoviridae family (5.88%) was recorded at MN-WWTP. Significant influence of temporal variations on prevalence of Myoviridae and Siphoviridae was detected in both WWTP and MN-WWTP, respectively. Highest phage prevalence was obtained in August (75%), followed by September (50%). Highest phage prevalence was recorded at a temperature range of 29-33°C. Significant influence of temperature on the prevalence of Myoviridae phages was detected at MN-WWTP. Four bacteriophages with various abundance levels were identified by NGS. Cronobacter virus Esp2949-1 was found first time with highest abundance (4.41%) in wastewater of Riyadh. Bordetella virus BPP1 (4.14%), Dickeya virus Limestone (1.55%) and Ralstonia virus RSA1 (1.04%) were also detected from samples of MN-WWTP. Highest occurrence of Bordetella virus BPP1 (67%) and (33.33%) was recorded at KSU-WWTP and MN-WWTP, respectively. Highest Bordetella virus BPP1 occurrence was recorded in September (50%) followed by August (40%). The findings of study showed new insights of phage diversity from wastewater sources and further large-scale data studies are suggested for comprehensive understanding.